دور الضبط الإداري في مواجهة الظروف الاستثنائية - مرهج، منار غسان; التركاوي، عمار خليل (جامعة البعث, 2017)
The theory of exceptional circumstances has emerged to enable the administrative control authorities to face the difficult crises and to provide them with the powers that allow them to take the measures required by the situation at the maximum speed, even if they contravene the ordinary laws, in order to preserve the objectives of the administration The defect that led to the disturbance of the general facility. The role of administrative control in the face of exceptional circumstances is of great importance. The legislator often extends these powers by constitutional provisions, such as those relating to the necessity regulations or special laws, such as emergency law and martial law.
ظهرت نظرية الظروف الاستثنائية لتمكن سلطات الضبط الإداري من مواجهة الأزمات العصيبة، ولتزويدها بصلاحيات تسمح له باتخاذ الإجراءات التي يتطلبها الموقف بالسرعة القصوى، ولو خالفت في ذلك القوانين العادية، وذلك من أجل المحافظة على أهداف الإدارة المتمثلة بالحفاظ على كيان الدولة واستمرارها وحماية النظام العام وإزالة الخلل الذي أدى إلى اضطراب سير المرفق العام. يكتسب الدور الذي يمارسه الضبط الإداري في مواجهة الظروف الاستثنائية أهمية كبيرة لذلك كثيراً ما يوسع المشرع من هذه السلطات بنصوص دستورية، كتلك المتعلقة بلوائح الضرورة أو بقوانين خاصة، كقانون الطوارئ والأحكام العرفية.
Keywords: الضبط الإداري -- الظروف الاستثنائية -- إدارة الأزمات -- القوانين العرفية -- حالة الطوارئ